EFFECTIVENESS OF OZONE THERAPY IN THE TREATMENT OF HERPETIC UVEITIS - Guliyeva, M.H.; Gasimov, E.M. (World of Medicine and Biology, 2023)
The purpose of the study was to learn the impact of ozone therapy on the outcomes of treatment in patients with herpetic uveitis. 80 patients (80 eyes involved) with herpetic uveitis were treated. The resorption of the infiltration of the choroid in the main group (40 patients – 40 eyes), was treated with ozone therapy in combination with conventional treatment terms of resorption of infiltration of the choroid were completed earlier than the compared group (40 patients – 40 eyes), which was treated with the preparation based on a combination of highly active enzymes of plant and animal origin combined with conventional treatment (respectively, 19.4±0.2 and 25.1±0.3; p